Análisis costo-efectividad del uso de estatinas frente a gemfibrozilo en pacientes de consultorios externos del Centro Médico Naval: "Cirujano Mayor Santiago Tavara" - Maguiña, Elbis (2006)
The purpose of this study was determine and comparing cost-effectiveness of Statins (Atorvastatin 20 mg and Pravastatin 20 mg) against Gemfibrozil 600 mg in hyperlipidemia treatment. This is a transversal, retrospective, descriptive study, carried out in the Centro Médico Naval "Santiago Távara" in the over a period from January 2002 to JuIy 2005. 64 patient's clinical record revision, who suffered with dyslipidemia of both genders, who were aged from 40 to 64 years old, attending in external medical service of Cardiology, Endocrinology. Geriatrics and Intemal Medicine, was carried out. According to cost-effectiveness analyses (for LDL-c level serumal reduction.), Statins showed a cost-effectiveness ratio of 13,76 nuevos soles for reduction percentage and Genúibrozil were not effective, it was not able to establish its cost-ffectiveness ratio. When effectiveness is measured for level reduction of trigLycerides, the Gemfibrozil showed a cost-effectiveness ratio of 1,74 soles for reduction percentage and Statins were not effective it was nol able to establish its cost - effectiveness ratio. When effectlveness is measured for therapeutic objective achievement according to Adults Third Panel (ATP III) of the National Cholesterol Education Program (NCEP 2001), Gernfibrozil shows a minar cost-effectiveness ratio (361,2 soles for patient), due to its low cost.